PENGARUH FESTIVAL PACU JALUR TERHADAP SOSIAL DAN EKONOMI MASYARAKAT DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Fajri Risaldi; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted to the community in Luai Village, Kuantan Mudik District, Kuantan Singingi Regency, especially at the Pacu Jalur Rayon III Festival in Kuantan Mudik District, Kuantan Singingi Regency. This research aims to know what kind of efforts that the communities do during the Pacu Jalur Festival and to know the effect of Pacu Jalur Festival on the communities’ social and economic. The theory used is Greenwood that consists of tourists visiting a place causing social interaction between local people and tourists which can lead to changes the patterns or values of communities’ life. This research uses a descriptive qualitative approach. This research was conducted in Luai Village, Kuantan Mudik District, Kuantan Singingi Regency. The subjects of this research were 12 people, namely 7 Traders, Head of Youth, Head of Luai Village, Kuantan Mudik Police Chief, Head of Kuantan Mudik district and 1 visitor. The sampling technique in this research is purposive sampling technique, where sampling was taken by selecting objects (informants) based on specific criteria which already set by the researcher. The sources of the data are Primary Data and Secondary Data. The analysis of the data used in this research is interactive data collection techniques. The results of this research are the efforts of communities at the Pacu Jalur Rayon III Festival in Luai Village, Kuantan Mudik district, Kuantan Singingi Regency are various such as selling the foods, drinks, selling the fruits, selling clothes of children and adults, and there are businesses such as provide of motorbike and car parking, provide of stands (paid viewing places) and also a children's playground or often called a balloon house. While the effect on communities’ social side is Pacu Jalur can be the way for communities to mutually friendly and enhance a sense of family. The effect of the Pacu Jalur festival on communities’ economic side is increasing of economic income and opening job vacancies.Keyword: Pacu Jalur, Economic Social, Kuantan Singingi Communities.